2017
DOI: 10.17576/pengurusan-2017-49-09
|View full text |Cite
|
Sign up to set email alerts
|

Kecerdasan Emosi dan Komitmen Afektif: Peranan Keterikatan Kerja sebagai Pengantara

Abstract: Matlamat kajian ini adalah untuk mengkaji hubungan secara langsung antara kecerdasan emosi dengan keterikatan kerja dan hubungan keterikatan kerja dengan komitmen afektif. Di samping itu, kajian ini juga bertujuan untuk mengkaji peranan keterikatan kerja sebagai pengantara terhadap hubungan antara kecerdasan emosi dengan komitmen afektif. Memandangkan masih kurang kajian empirikal dijalankan dalam mengkaji peranan keterikatan kerja sebagai pengantara terutamanya di antara hubungan kecerdasan emosi dengan komit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 19 publications
2
4
0
3
Order By: Relevance
“…Employees with a high level of affective commitment tend to have a strong attachment to the company. This is in line with research conducted by Bamiati (2020), Baker (2017)., Utami (2020), Herminingsih (2020), Putri (2019), Hasanati (2017), Diniyati (2018), Sutiyem et al (2020), and Ruslan et al (2019) shows that employee engagement has a positive and significant effect on affective commitment. H2: Employee engagement has a positive and significant effect on affective commitment to employees of PT.…”
Section: Figure 1 Conceptual Frameworksupporting
confidence: 90%
See 1 more Smart Citation
“…Employees with a high level of affective commitment tend to have a strong attachment to the company. This is in line with research conducted by Bamiati (2020), Baker (2017)., Utami (2020), Herminingsih (2020), Putri (2019), Hasanati (2017), Diniyati (2018), Sutiyem et al (2020), and Ruslan et al (2019) shows that employee engagement has a positive and significant effect on affective commitment. H2: Employee engagement has a positive and significant effect on affective commitment to employees of PT.…”
Section: Figure 1 Conceptual Frameworksupporting
confidence: 90%
“…This can arise based on the wishes of the employee caused by a sense of emotional attachment to the company and this can lead to a sense of engagement with work (Bamiati, 2020). Affective commitment is related to individual psychological aspects such as emotions, motivation and pleasure in attachment and the desire to be part of the organization (Baker & Ibrahim, 2017). Employees with a high level of affective commitment tend to have a strong attachment to the company.…”
Section: Figure 1 Conceptual Frameworkmentioning
confidence: 99%
“…Police who have high emotional intelligence wished to stay in organisations because they believe their salary will increase and not willing to lose retirement benefits. Baker and Ibrahim (2017) also agreed that intrapersonal emotional intelligence highly related to affective commitment. In contrast, Baker (2010) revealed that there was a strong relationship between job commitment and interpersonal emotional intelligence.…”
Section: Emotional Intelligence and Job Commitmentmentioning
confidence: 76%
“…Emotional intelligence correlated to job commitment (Baker, 2010;Baker & Ibrahim, 2017;Yaacob, 2012). Yaacob (2012) found that intrapersonal emotional intelligence significantly predicts job commitment despite the organisational factors.…”
Section: Emotional Intelligence and Job Commitmentmentioning
confidence: 99%
“…Emotional intelligence and affective commitment are two factors that are always associated with the emotions of an individual (Baker & Ibrahim, 2017). Therefore, the objective of this study is:…”
Section: R E S E a R C H O B J E C T I V E Smentioning
confidence: 99%